2019
DOI: 10.1002/jcp.29104
|View full text |Cite
|
Sign up to set email alerts
|

PCBP2 promotes the development of glioma by regulating FHL3/TGF‐β/Smad signaling pathway

Abstract: The purpose of this study was to investigate the role of Poly (C)-binding protein 2 (PCBP2) and the related signaling pathway in glioma progression. Quantitative realtime polymerase chain reaction (qRT-PCR) and immunohistochemistry (IHC) were performed to measure PCBP2 messenger RNA and protein expression in glioma tissues or cells. Cell transfection was completed using Lipofectamine 2000. 3-(4, 5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, Transwell assay and flow cytometry assay were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…FHL3 interacts with transcription factors and multiple cell‐signalling molecules in glioma, breast cancer, and liver cancer 9,10,23 . Although most studies mentioned that FHL3 is a tumour suppressor, we identified that FHL3 promotes NSCLC cell proliferation and invasion, potentially affecting the biological behaviour of NSCLC cells by disturbing the cell cycle via P27 and invasion by the TGF‐β signalling pathway, as reported in other studies 10,11 . Meanwhile, the tumour‐promoting effect of FHL3 is closely correlated with the survival rate and prognosis.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…FHL3 interacts with transcription factors and multiple cell‐signalling molecules in glioma, breast cancer, and liver cancer 9,10,23 . Although most studies mentioned that FHL3 is a tumour suppressor, we identified that FHL3 promotes NSCLC cell proliferation and invasion, potentially affecting the biological behaviour of NSCLC cells by disturbing the cell cycle via P27 and invasion by the TGF‐β signalling pathway, as reported in other studies 10,11 . Meanwhile, the tumour‐promoting effect of FHL3 is closely correlated with the survival rate and prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…According to reports by Niu 10 and Mao, 11 genes such as P27, TGF‐β, and Smad2/3 are the downstream targets of FHL3. We examined expression of these genes in NSCLC cells and found that FHL3 overexpression inhibited P27 expression, disturbing the cell cycle and promoting the expression of TGF‐β and Smad2/3—all of which promote cell invasion (Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the TGF-beta pathway is significantly activated in malignant gliomas, and the activation of TGF-beta pathway was closely associated with malignant progression and poor prognosis ( Roy et al, 2015 ). The experimental study demonstrated that PCBP2 could activate TGF-beta pathway, thus promoting the development and progression of glioma ( Mao et al, 2020 ). In summary, the aforementioned results showed that TRMT6 may be involved in glioma progression by regulating cell cycle, PI3K-AKT, TGF-beta, MTORC1, NOTCH, and MYC pathways.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b is overexpressed in glioblastoma, and its elevated expression is associated with the increased histologic grade of GBM (6). TGF-b promotes proliferation, invasion, metastasis, angiogenesis, resistance to apoptosis, replicative immortality, evasion of growth suppression, evasion of immune checkpoint blockade, and chemoresistance in GBM (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%